2003
DOI: 10.1290/1543-706x(2003)039<0291:foapcc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

FORTIFICATION OF a PROTEIN-FREE CELL CULTURE MEDIUM WITH PLANT PEPTONES IMPROVES CULTIVATION AND PRODUCTIVITY OF AN INTERFERON-γ–PRODUCING CHO CELL LINE

Abstract: A strong tendency is currently emerging to remove not only serum but also any product of animal origin from animal cell culture media during production of recombinant proteins. This should facilitate downstream processing and improve biosafety. One way consists in the fortification of protein-free nutritive media with plant protein hydrolysates. To investigate the effects of plant peptones on mammalian cell cultivation and productivity, CHO 320 cells, a clone of CHO K1 cells genetically modified to secrete hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 29 publications
7
54
0
Order By: Relevance
“…YP.A displayed concentrations of 5.1 9 10 6 cell mL -1 and 4.7 9 10 6 cell mL -1 , respectively, after only 90 h. During the first phase of culture (0-45 h) cells grew at a similar maximal specific rate of 0.04 h -1 whatever culture medium (Table 1). Several studies confirmed that maximal specific growth rates of CHO cells cultivated in Erlenmeyer flask were not enhanced by addition of YE or plant peptones (Sung et al 2004;Burteau et al 2003;Kim and Lee 2009). However, in the present study, the specific cell growth rate in control culture decreased from 0.04 h -1 to 0.01 h -1 during the phase from 45 to 80 h, while hydrolysates sustained its maximal value until 80 h of culture (Table 1).…”
Section: Kinetics Of Cho Cell Growth and Deathsupporting
confidence: 81%
See 4 more Smart Citations
“…YP.A displayed concentrations of 5.1 9 10 6 cell mL -1 and 4.7 9 10 6 cell mL -1 , respectively, after only 90 h. During the first phase of culture (0-45 h) cells grew at a similar maximal specific rate of 0.04 h -1 whatever culture medium (Table 1). Several studies confirmed that maximal specific growth rates of CHO cells cultivated in Erlenmeyer flask were not enhanced by addition of YE or plant peptones (Sung et al 2004;Burteau et al 2003;Kim and Lee 2009). However, in the present study, the specific cell growth rate in control culture decreased from 0.04 h -1 to 0.01 h -1 during the phase from 45 to 80 h, while hydrolysates sustained its maximal value until 80 h of culture (Table 1).…”
Section: Kinetics Of Cho Cell Growth and Deathsupporting
confidence: 81%
“…Nevertheless, the risk of contamination by viruses, mycoplasma or prions from animal supplement led to a strong demand for media formulations free from animal components (Grillberger et al 2009). Then, the search for culture media that most closely replicated the benefits of animal-derived sera without their biosafety risks provoked a growing interest in the use of plant peptones (Heidemann et al 2000;Burteau et al 2003;Farges et al 2008) or yeast extracts (YE) (Sung et al 2004;Kim and Lee 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations